2022
DOI: 10.3390/ma15124341
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkaline Earth Metals on Structure Formation and Magnesium Alloy Properties

Abstract: The main aim of this work is to improve the structure and properties of the magnesium alloy ML5 by modifying it with alkaline earth metals (ALM). The separate and joint influence of calcium and barium on the macrostructure and microstructure of the alloy of Mg-Al-Zn system was investigated. The qualitative and quantitative estimation of the structural components was carried out. Alkali earth metals were included in complex intermetallic phases and serve as additional crystallization centers. Modification of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…These devices use manufacturing processes such as machining, casting, polishing, metal injection moulding and rapid manufacturing. For these reasons, medical devices continue to become smaller and smaller [6,7]. Features and components of a few microns require specialist processes of micromanufacturing, which include micromachining and micromoulding.…”
Section: Introductionmentioning
confidence: 99%
“…These devices use manufacturing processes such as machining, casting, polishing, metal injection moulding and rapid manufacturing. For these reasons, medical devices continue to become smaller and smaller [6,7]. Features and components of a few microns require specialist processes of micromanufacturing, which include micromachining and micromoulding.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the phase diagrams of binary systems of silver and gold with magnesium showed that they can form solid solutions, as well as new intermetallic phases. These phases have higher melting points compared to magnesium, therefore they act as additional crystallization centers during the initial period of crystallization, thus refining the grain and positively affecting the properties of the metal [29].…”
Section: Introductionmentioning
confidence: 99%